COMMUNITY BASED DISASTER RISK MANAGEMENT: AN APPROACH TO ACHIEVE DISASTER RISK REDUCTION UNDER SENDAI FRAMEWORK (2015-2030). - Suman Das; Nain, Gaurav; Suraj Prasad (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Even with the increasing scientific and technological knowledge in the present times, reducing the impact of natural disasters is a difficult task. Community Based Disaster Risk Management (CBDRM) is an integral part of sustainable development, which puts communities at the centre of decision making regarding identification, assessment and management of disaster risks at the local level. Although disasters affect large areas, their impacts are severe even at the local level. The present paper deals with the concept of community based disaster risk management process after implementation of the programme in an area of ​​Chamoli district of Uttarakhand. The methodology is basically proposed in two phases: Firstly assessment of community vulnerabilities, multi hazard capacity in the selected village by community participation and secondly training and skill development for multi hazard and disaster risk mitigation by community participants.